Síndrome de taquicardia ortostática postural. Presentación de un caso clínico. Postural orthostatic tachycardia syndrome. Presenting a clinical case. - Sherien Sixto Fernández; José A. Valdés Rucabado; Juan J. Quirós Luis; Julio Oscar Cabrera-Rego; Karel Díaz Reyes (ECIMED, 2011)
Patients with postural orthostatic tachycardia syndrome present a sustained heart rate increaseduring orthostasis. We present a patient with previous history of recurrent syncopediagnosed with postural orthostatic tachycardia syndrome using the Tilt-test. Beta-Blockerstreatment was effective and helped the patient to stay asymptomatic.